2016
DOI: 10.5455/jice.20160331064446
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial activity of five essential oils on multi-drug resistant Gram-negative clinical isolates

Abstract: Aim/Background:The emergence of drug-resistant pathogens has drawn attention on medicinal plants for potential antimicrobial properties. The objective of the present study was the investigation of the antimicrobial activity of five plant essential oils on multidrug resistant Gram-negative bacteria.Materials and Methods:Basil, chamomile blue, origanum, thyme, and tea tree oil were tested against clinical isolates of Acinetobacter baumannii (n = 6), Escherichia coli (n = 4), Klebsiella pneumoniae (n = 7), and Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 33 publications
3
46
0
5
Order By: Relevance
“…Acinetobacter baumannii NCTC 12156 also showed resistance against gentamicin, although tea tree, thyme, rosewood, clove, cinnamon bark and cinnamon leaf EOs all produced zones ≥17 mm. These data are in line with published reports (Doran et al ; Adukwu et al ; Priti and Shridhar ; Yap et al ; Sakkas et al ), which indicate that EOs are capable of working effectively against bacteria resistant to commercial antibiotics.…”
Section: Discussionsupporting
confidence: 92%
“…Acinetobacter baumannii NCTC 12156 also showed resistance against gentamicin, although tea tree, thyme, rosewood, clove, cinnamon bark and cinnamon leaf EOs all produced zones ≥17 mm. These data are in line with published reports (Doran et al ; Adukwu et al ; Priti and Shridhar ; Yap et al ; Sakkas et al ), which indicate that EOs are capable of working effectively against bacteria resistant to commercial antibiotics.…”
Section: Discussionsupporting
confidence: 92%
“…These acids can change membrane proteins then block their normal functions (Nazaro et al, 2013). Similarly, essential oils are rich in phenolic compounds that can affect structure and unsaturated fatty acids of bacteria cell wall (Sakkas et al, 2016). Results also show that thyme and Boswellia contain flavonoid compounds such as hispertin (38.5 ppm in thyme and 12.1 ppm in Boswellia), narengin (975.9 ppm in thyme and 7.5 ppm in Boswellia).…”
Section: Resultsmentioning
confidence: 78%
“…Similarly, Nazzaro et al (2013) reported that rod-shape bacteria are generally sensitive for essential oils with antibacterial properties, but in this study, most K. pneumoniae isolates which are rod-shaped showed resistant response against the tested extracts. Many bioactive compounds such as thymol, carvacol, flavoinds, biphenyls and aliphatic phenols are found in thymus species (Nadia et al, 2013) while Sakkas et al (2016) noted that the inhibitory effects of thyme are due to thymol, p-cymene and linalool compounds. Most of the antimicrobial activity in Thymus essential oil appears to be associated with phenolic compounds (thymol and carvacol); however, in some cases an elevated concentration in these components does not necessarily increase the antimicrobial properties (Rota et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on the utilization of natural antioxidants (e.g., herbal essential oils and extracts) indicate their capacity and safety [3,4]. Also, the antimicrobial properties of natural substances such as plant essential oils and extracts have been extensively studied with promising results [5]. The proper recycling and use of fruit-processing plants by-products like fruit seeds or skins discarded and piling up in huge amounts every year, are of great interest for the food industry, particularly their potential to be a useful source of oil and meal [6].…”
mentioning
confidence: 99%